2019
DOI: 10.1302/0301-620x.101b12.bjj-2019-0493.r1
|View full text |Cite
|
Sign up to set email alerts
|

No effect on functional outcome after repair of pronator quadratus in volar plating of distal radial fractures: a randomized clinical trial

Abstract: Aims The aim of this study was to investigate the difference in functional outcome after repair and non-repair of the pronator quadratus muscle in patients undergoing surgical treatment for a distal radial fracture with volar plating. Patients and Methods A total of 72 patients with a distal radial fracture were included in this randomized clinical trial. They were allocated to have the pronator quadratus muscle repaired or not, after volar locked plating of a distal radial fracture. The patients, the assessor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 21 publications
1
31
0
4
Order By: Relevance
“…Regarding pronation strength, two studies showed that the pronation strength in the group without PQ repair decreased significantly only in the patients with AO/ OTA type B fractures but not in those with AO/OTA type C fractures [22,25]. One study included patients with AO/OTA type A2, A3, and C1 fractures [18], while another study included patients with AO/OTA type A2, A3, C1-3 fractures [10]. Having better repair quality with preoperatively intact and nicely prepared PQ flaps seems logical.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding pronation strength, two studies showed that the pronation strength in the group without PQ repair decreased significantly only in the patients with AO/ OTA type B fractures but not in those with AO/OTA type C fractures [22,25]. One study included patients with AO/OTA type A2, A3, and C1 fractures [18], while another study included patients with AO/OTA type A2, A3, C1-3 fractures [10]. Having better repair quality with preoperatively intact and nicely prepared PQ flaps seems logical.…”
Section: Discussionmentioning
confidence: 99%
“…Although the durability of PQ repair has been supported [5], ensuring good-quality repair, especially in comminuted DRFs with frayed PQ muscles, is sometimes difficult. Two RCTs routinely checked the length or retraction of the PQ in ultrasonography examinations [10,18]. In our included studies, patients in the group without PQ repair who had more metaphyseal displaced and complex fracture patterns had better pronation strengths (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because pronator teres is the main muscle of forearm pronation [17], the loss of pronator teres can be compensated by pronator teres, so that forearm rotation can be preserved. Many studies also believe that suture of pronator anterior muscle may not give patients better function and mobility [18][19][20].…”
Section: Discussionmentioning
confidence: 99%